Clinical proteomics in the investigation of bladder cancer - Vlahou, Antonia (Henry Stewart Talks, 2013)
Clinical proteomics: principles of experimental design and data reporting, Clinical needs in bladder cancer, Bladder Cancer Biomarker discovery in urine using proteomics approaches, How to progress towards implementation